Determinants of the Millennial Muslim Generation's Literacy Level on Cash Waqf in Bandung City - Muhammad Ilham Rasyid; Juliana Juliana; Rida Rosida; Firman Menne; M. Hatta; Qudratov Inomjon (KEDJATI Foundation, 2025)
This study is intended to determine the level of cash waqf literacy for the generation of millennial Muslims in Bandung. Besides, this study aims to decide the level of education, religiosity, and access to information media that influence the literacy of cash waqf for the generation of millennial Muslims in Bandung. The subject of this research is the Muslim community born in 1980 to early 2000, with 100 respondents. The method used in this research is causality with a quantitative approach. The data analysis technique used is Multiple Linear Regression. The results showed that the waqf literacy of the generation of millennial Muslims in Bandung was in the medium category, and based on multiple linear regression analysis, it showed that together, the variables of education level, level of religiosity, and access to information media had a significant effect on the variable of money waqf literacy. This research is expected to provide benefits for the Indonesian Waqf Board (BWI), other waqf institutions, and Islamic Financial Institutions Receiving Cash Waqf (LKS-PWU) in reviewing the literacy of cash waqf in society so that it can be used as an illustration in the strategy of collecting cash waqf.